KUALITAS AUDIT: KONSENTRASI PASAR AUDIT, UKURAN PERUSAHAAN, DAN WORKLOAD - Farah Atya Raihani (2023)
This study is quantitative research aimed to determine the influence of audit market concentration, firm size, and workload on audit quality. The data used in this study is secondary data of annual financial reports of all go public companies listed on the Indonesia Stock Exchange (IDX) during 2021 and obtained 734 companies that fit the criteria as a sample. The method used in this research is logistic regression analysis using Eviews 8 software. Based on the results of testing all hypotheses, it is showed that partially the firm size variable has a significant positive effect on audit quality. Meanwhile, audit market concentration and workload variables have no effect on audit quality.